Clinical Legal Education at the Faculty of Syariah and Law, Universiti Sains Islam Malaysia - Supaat, Dina I (The Indonesian Journal of International Clinical Legal Education, 2019)
Clinical Legal Education (CLE) is based on the idea that lawpractice requires thinking and doing. It is founded on thenotion of learning by doing in which law students gainlawyering skills by performing lawyering tasks andresponsibilities. This method gives students the opportunity towork on actual and simulated cases and solve legal problemssystematically. This paper discusses the implementation andapplication of CLE at the Faculty of Syariah And Law, UniversitiSains Islam Malaysia with emphasis on Problem-basedlearning, specifically relating to its process, model of PBLactivities, targeted skills, student assessment and studentfeedback. Discussion also covers benefit and challenges ofapplying CLE and PBL at the faculty. It discusses the experienceof the instructor in applying PBL in two courses. This papercomes up with suggestion on the application andimplementation of the method in a law school so that lawstudents can master practical legal skills in order to be moreemployable.